2020
DOI: 10.1038/s41598-020-73496-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of slope aspect on vegetation attributes in a mountainous dry valley, Southwest China

Abstract: Slope aspect plays a critical role in influencing vegetation pattern in semiarid area. The dry valleys of the Hengduan Mountains Region, southwestern China, are striking geographical landscape, suffering from severe ecological degradation. Here, we comprehensively investigated how slope aspect affects vegetation attributes in one of these valleys- the dry valley in the upper reaches of Min River. Three sites were selected along the valley and we quantitively examined the vegetation difference between slope asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 58 publications
2
42
0
Order By: Relevance
“…The amount of incident solar radiation can also affect the temperature of the soil and air at the ground's surface [ 49 ]. Soil temperature has a significant impact on plant growth and establishment (such as seed germination and root growth) [ 52 ]. Forest structures on northeast and south-west facing slopes are expected to differ due to differences in the duration and intensity of incoming solar radiation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amount of incident solar radiation can also affect the temperature of the soil and air at the ground's surface [ 49 ]. Soil temperature has a significant impact on plant growth and establishment (such as seed germination and root growth) [ 52 ]. Forest structures on northeast and south-west facing slopes are expected to differ due to differences in the duration and intensity of incoming solar radiation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Slope aspect is an important topographic factor that underlies the variation of vegetation composition and attributes and contributes to the substantial heterogeneity of landscape and high species diversity at the local scales (Li et al., 2011 ; Sidari et al., 2008 ; Singh, 2018 ; Warren, 2008 ; Warren II, 2010 ; Yang et al., 2020 ). For example, the previous studies have shown a higher richness and coverage of forbs species on north‐facing slopes (NFS) compared with south‐facing slopes (SFS; Li et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aspect indicates the orientation of a slope to the sun, therefore suggesting the level of incident sunlight radiation on it, while altitude is a highly influential topographic attribute on the abiotic factors of an environment [40]. Aspects and altitude determine the microclimate of an area, and thus play an important role in vegetation patterns of productivity, species composition and biodiversity [41][42][43], and soil chemical, physical, and biological parameters [44][45][46], all of which are essential attributes used to assess grassland health, especially in a highly heterogeneous environment such as LUMGS.…”
Section: Rich Picturementioning
confidence: 99%